2009
DOI: 10.1186/1756-8722-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Radical cyberknife radiosurgery with tumor tracking: an effective treatment for inoperable small peripheral stage I non-small cell lung cancer

Abstract: ObjectiveCurative surgery is not an option for many patients with clinical stage I non-small-cell lung carcinoma (NSCLC), but radical radiosurgery may be effective.MethodsInoperable patients with small peripheral clinical stage I NSCLC were enrolled in this study. Three-to-five fiducial markers were implanted in or near tumors under CT guidance. Gross tumor volumes (GTVs) were contoured using lung windows. The GTV margin was expanded by 5 mm to establish the planning treatment volume (PTV). A dose of 42–60 Gy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 43 publications
4
68
1
Order By: Relevance
“…Whyte et al reported three patients with pneumothoraces; two were managed expectantly but one required chest tube placement [28]. Collins et al and Pennathur et al reported a pneumothorax requiring tube thoracostomy in 25 and 28% of their patients, respectively [29,30].…”
Section: Percutaneous Intrapulmonal Placementmentioning
confidence: 97%
“…Whyte et al reported three patients with pneumothoraces; two were managed expectantly but one required chest tube placement [28]. Collins et al and Pennathur et al reported a pneumothorax requiring tube thoracostomy in 25 and 28% of their patients, respectively [29,30].…”
Section: Percutaneous Intrapulmonal Placementmentioning
confidence: 97%
“…No proper comparison of SABR and segmentectomy functional consequences can be performed because of the lack of randomised trials. Several studies report PFT measured before and after SABR, but a comparison with surgical series is hazardous because of strong differences in patient characteristics ( patients in SABR studies are older and have more degraded lung function) and study design [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The SABR PFT results suggest that the mean loss of lung function may be lower after SABR than after segmentectomy, but this needs to be confirmed.…”
Section: Future Prospectsmentioning
confidence: 99%
“…CK treatment has been shown to be very effective for stage Ⅰ NSCLC in several studies published over the last few years (3,4,6,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…All the stage I NSCLC patients were implanted using fiducial markers with the Synchrony ® Respiratory Motion Tracking system (6). Under conscious sedation and local anesthesia, 3-5 gold fiducials measuring 0.8 mm in diameter by 3 mm in length (Civco Medical Solutions, Orange City, IA, USA) were placed with adequate spacing (1-2 cm) in or near tumours under CT guidance (7,8).…”
Section: Methodsmentioning
confidence: 99%